Comparison of 5G Network Throughput on Varying Cluster Size - Yaser, Muhammad (Electrical Engineering, Universitas Mercu Buana, 2024)
Abstract – The development of cellular technology is accelerating, as is the exponential increase in data traffic, resulting in the creation of the following technology, namely 5G. This study looks at the throughput of the 5G network in various cluster sizes. In this study, integer frequency reuse (IFR) with a bandwidth of 100 MHz and a frequency of 3.5 GHz was used. The path loss Urban Macro (UMa) based on 3GPP 38.901 is employed in this study. The data was assessed and compared using computer simulations, and a comparison of throughput CDF values for each cluster size was obtained. When CDF = 0.9, the throughput of the N = 3 scenario is 6480 bps, which is greater than the huge throughput of the N = 4 scenario of 4860 bps and the large throughput of the N = 7 scenario of 2777 bps. According to the simulation, the cell with N = 3 cluster size has a greater throughput than the other scenarios. The cell with the smallest cluster size had the maximum throughput, whereas the largest had the lowest.